2017
DOI: 10.1158/1541-7786.mcr-16-0358
|View full text |Cite
|
Sign up to set email alerts
|

Pathology-Driven Comprehensive Proteomic Profiling of the Prostate Cancer Tumor Microenvironment

Abstract: Prostate cancer is the second most common cancer in men worldwide. Gleason grading is an important predictor of prostate cancer outcomes and is influential in determining patient treatment options. Clinical decisions based on a Gleason score of 7 are difficult as the prognosis for individuals diagnosed with Gleason 4+3 cancer is much worse than for those diagnosed with Gleason 3+4 cancer. Laser capture microdissection (LCM) is a highly precise method to isolate specific cell populations or discrete microregion… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 62 publications
(65 reference statements)
0
14
0
Order By: Relevance
“…Recent developments in mass spectrometric methods 11 13 have enabled high throughput analysis of clinical patient samples, and the first integrative studies involving large scale, mass spectrometry-based proteomics of human cancer have recently been published 14 16 . For prostate cancer, recent proteomic advancements have included high scale, mass spectrometry-based studies performed in diagnostic body fluids 17 , 18 , as well as primary tumors 19 and the tumor microenvironment 20 . So far, the only integrative proteogenomic analysis of clinical prostate cancer involved genomic and transcriptomic data of CRPC combined with phosphoproteomic analysis 21 .…”
Section: Introductionmentioning
confidence: 99%
“…Recent developments in mass spectrometric methods 11 13 have enabled high throughput analysis of clinical patient samples, and the first integrative studies involving large scale, mass spectrometry-based proteomics of human cancer have recently been published 14 16 . For prostate cancer, recent proteomic advancements have included high scale, mass spectrometry-based studies performed in diagnostic body fluids 17 , 18 , as well as primary tumors 19 and the tumor microenvironment 20 . So far, the only integrative proteogenomic analysis of clinical prostate cancer involved genomic and transcriptomic data of CRPC combined with phosphoproteomic analysis 21 .…”
Section: Introductionmentioning
confidence: 99%
“…With a larger sample size (n = 16 for high-risk PCa and n = 12 for low risk PCa), Iglesias-Gato et al found that 130 proteins were differentially ( p < 0.05 and FC > 1.6) expressed between low-risk and high-risk PCa groups [11]. Via label-free quantitative proteomics comparison of LCM-isolated epithelial cells from Gleason grade 3 versus 4 tumors (n = 4 for each), Staunton et al identified 120 DEPs (FDR < 0.05) [12]. A comparison of the three datasets suggested that only three DEPs (ADH5, ALDH2, and CSRP1) are shared between our and Iglesias-Gato studies, three DEPs (CPE, QDPR, and PACSIN3) are shared between our and Staunton studies, and five DEPs (ABAT, COL6A2, COL6A3, EPHX2, and PFKP) are shared between the Iglesias-Gato and Staunton studies (Additional file 2: Table S6).…”
Section: Discussionmentioning
confidence: 99%
“…Despite the small number of clinical samples analyzed and limited proteome coverage, some proteins like MYO6 were found as differentially regulated between ERG+ and ERG− tumors ( 11 ). Another example of initial proteomic study tackling a relevant PCa question is the analysis of epithelial and microenvironment tissue that were micro-dissected from tumors graded with different Gleason scores ( 12 ). Despite similar limitations as the previously described study, this investigation served as a proof of principle for the existence of major differences in tumor microenvironment.…”
Section: Proteomic Profiling Of Pca Tissuesmentioning
confidence: 99%